Analyzing the Determinants of the Willingness to Receive and Pay for COVID-19 Vaccines Prior to the Commencement of Vaccination in Indonesia Using a Mixed-method Study - Romadhon, Yusuf Alam; Lestari, Nining; Firdausi, Nida Faradisa; Kurniati, Yuni Prastyo (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: The occurrence of various deceptive news on COVID-19 vaccines adversely impact public mindset. Prior to the mass vaccination of Indonesian government, perception of the willingness to be vaccinated and its determinant were not widely explored.Objectives: This study is aimed at evaluating the determinants of willingness to receive and pay for COVID-19 vaccines, prior to the commencement of widespread vaccination in Indonesia.Method: This study applied a cross-sectional design to assess the inhibiting factors of both the willingness to receive and pay for COVID-19 vaccines. Statistical analysis was conducted using bivariate and multivariate methods. Furthermore, a qualitative approach was also adopted to categorize open-ended themes on the determinant of willingness to pay for COVID-19 vaccines.Results: Based on the determinants of willingness to be vaccinated, the following results were obtained, including the occupation of health workers (OR=3.638; p=0.000), civil servants (OR=1.776; p=0.030), perception on COVID-19 as dangerous (OR=2.161; p=0.010), perception on the vaccines as effective (OR= 13,156; p=0.000), perception on vaccine as safe (OR=15,769; p=0.000). In terms of the determinants of willingness to pay, the following results were recorded, including respondents’ age of 40 years (OR=2.048; p=0.000), income of IDR.2,500,000 (OR=1.631;p=0.002), experience from the interaction with COVID-19 patients (OR=1.422; p=0.013), perception on the virus as dangerous (OR=2.211; p=0.000), perception on health protocol discipline (OR=1.834; p=0.014), and perception on the vaccine as effective (OR=1.760; p=0.011). Furthermore, 6 concerns were raised on the willingness/reluctance to pay for the vaccine, such as the perception of the vaccines’ effectiveness and safety, equity, suspicion surrounding the pandemic and vaccine, optional measures in combating the outbreak, personal circumstances and nationalism. Conclusion: The determinants of willingness to receive the COVID-19 vaccine included the occupation of health workers and civil servants, perception of the disease as dangerous, perception of the vaccine as effective and safe. Meanwhile, the factors of willingness to pay included the age range of 40 years, high income, interaction with COVID-19 patients, perception of health protocol discipline and the vaccines’ effectiveness.